ESCRT-III-dependent and -independent egress of herpesviruses - Arii, Jun (Frontiers in Virology, 2024)
Enveloped viruses complete their replication cycle by forming virions that bud from infected cells through membrane scission. The mechanisms by which this is achieved are less well-understood than the well-characterized membrane scission of vesicles budding inwards into the cytosol. The scission of vesicles that bud away from the cytosol is mediated by machinery of the endosomal sorting complexes required for transport (ESCRT)-III, which is highjacked by viruses of several different families. Other groups of viruses can bud independently of ESCRT-III activity. It has not been fully elucidated how the latter achieve this in the absence of host ESCRT-III, but it is known that some viral proteins directly mediate membrane scission. The Herpesviridae constitute a family of highly diverse viruses that bud at the inner nuclear membrane and cytoplasmic membranes in infected cells. Many investigators have attempted to determine the mechanism of membrane scission during herpesvirus budding, and have found this to be complex, not exactly conforming to either of the two methods. The present review attempts to synthesize the disparate findings into a model of herpesvirus egress based on both ESCRT-mediated and viral protein-mediated mechanisms.